If it's not what You are looking for type in the equation solver your own equation and let us solve it.
15y=9y+24
We move all terms to the left:
15y-(9y+24)=0
We get rid of parentheses
15y-9y-24=0
We add all the numbers together, and all the variables
6y-24=0
We move all terms containing y to the left, all other terms to the right
6y=24
y=24/6
y=4
| 4d-(3-6d)=4d-3+6d | | 8p+9=2p-27 | | x+77+31=180 | | G(x)=11–3x+2 | | -8g+6=3g−5 | | 10+2m=m | | 5b-(3-6b)=5b-3+6b | | (7x+6)+(8x+2)=41 | | -18=6+8x+4x | | 3x-(2x-6)=3x-2x+6 | | F(x)=1.5+1 | | 19-x=31 | | q+|64|=9.6 | | -5+7=-4(2y+2) | | h-6+7h=-15 | | 0-x/10=13 | | q+64=9.6 | | 9x+12-5x/2=32 | | 9-x=10+9 | | -15-12-4x+1=89 | | 6(3p+5)-8p=5(2p+6) | | 6x-4(x-3)=2(x+6 | | -77=-8(1-8x)+(8x+5) | | 4x=7x7 | | 1+5k=71 | | -77=-8x)+5(6x+5) | | (3y-43)=62 | | 1.5=18-2x | | 5x-9=15-11x | | 65=x+55 | | 3(6x-10)=5(3x-3) | | 68-4x=3(4+x) |